Serpin7 controls egg diapause of migratory locust (Locusta migratoria) by regulating polyphenol oxidase. Issue 5 (24th March 2020) - Chen, Jun; Cui, Dongnan; Ullah, Hidayat; Hao, Kun; Tu, Xiongbing; Zhang, Zehua
Abstract : Diapause is a state of arrested growth, which allows insects to adapt to diverse environments. Serine protease inhibitors (serpins) play an important role in various physiological processes, including blood coagulation, fibrinolysis, development, complement activation and extracellular matrix remodeling. We hypothesized that serpin may affect energy metabolism and thereby control diapause of migratory locust ( Locusta migratoria ) embryos by regulating protease cascades. A total of seven nonredundant serpin genes (named serpin1 – serpin7 ) of L. migratoria were obtained through transcriptomic analysis. We further performed label‐free proteomic sequencing and analysis of diapause and nondiapause eggs of L. migratoria, revealing significant differences in serpin7 expression. A significant reduction in diapause rate under the short photoperiod was observed in insects treated with serpin7 double‐stranded RNA. Furthermore, knockdown of the serpin7 gene resulted in significant upregulation of the activity of polyphenol oxidase. We therefore propose that the observed serpin7 gene plays a crucial role in diapause, suggesting that control of energy metabolism may have potential as a future strategy for the reproductive control of insect pests. Abstract : Lm_Serpin7, a member of the Serpin protease inhibitor family, is highly expressed in diapause eggs and plays an important role in Locusta migratoria egg diapause. Knockdown of Lm_Serpin7 by injection with ds_ serpin7 decreases egg diapause rate, suggesting that control of Lm_Serpin7 may have potential as a future strategy for the reproductive control of insect pests.